THE USE OF THREE PHASES TECHNIQUE TO IMPROVE STUDENTS’ PARTICIPATION AND READING COMPREHENSION IN NARRATIVE TEXT (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2013)
This article is about the use of three phases technique to improve students’ participation and reading comprehension in narrative text. In order to achieve the objectives of this research, the writer adopted and action research design. The subject of this research was class 8G of SMP N 30 Semarang in the academic year 2012/2013 which consist of 37 students. There were two cycles with four phases in each cycle. They were planning, acting, observing and reflecting. The instrument for collecting data, the writer used observation checklist, field notes, test, questionnaire and documentation. The result of this study showed that three phases technique could improve students’ participation and reading comprehension in narrative text. Three phases technique namely pre reading, while reading and post reading can lead the students be more active and enthusiastic during teaching and learning process. By using three phases technique, students easily understand the content of the text and also they were active asking and giving their argument about narrative text.